PENGARUH PENDIDIKAN KESEHATAN MENGGUNAKAN MEDIA E-BOOK TERHADAP PENGETAHUAN IBU HAMIL TENTANG PELAYANAN PEMERIKSAAN KEHAMILAN PADA MASA PANDEMI COVID-19 - Dina Rosalina; Suryani Suryani; Enny Susilawati; Ruwayda Ruwayda (NHM PRESS, 2022)
The application of ANC visit behavior according to the protocol is certainly strongly influenced by the knowledge of pregnant women about ANC during a pandemic. One way that can be done to increase the knowledge of pregnant women about pregnant women's health services is by providing online health education. One of them is by providing e-book media or electronic books. This study uses a pre-experimental design that is one group pretest-posttest to see the effect of health education using e-book media on the knowledge of pregnant women about antenatal care services during the covid-19 pandemic. This research will be conducted at the Putri Ayu Health Center, Jambi City in February-June 2022. The population of this study was all pregnant women at the Putri Ayu Health Center, which were 104 people. The sample size using the Slovin formula as many as 57 people, taking the sample using the Quata sampling technique. The instrument used in this research is filling out a questionnaire or questionnaire. The data analysis in this study was univariate and bivariate using the T-test. Based on the results of the study, it can be seen that before being given health education using e-books, most of the respondents had low knowledge of 44 respondents (77.2%) and after most of them had high knowledge of 31 respondents (54.4%). The results of the statistical test are known to have an p-value of 0.000, which means that there is an effect of health education using e-book media on the knowledge of pregnant women about antenatal care services during the COVID-19 pandemic at the Putri Ayu Health Center, Jambi City. From the results of the study, it can be concluded that there is an effect of health education using e-book media on the knowledge of pregnant women about antenatal care services during the covid-19 pandemic at Putri Ayu Health Center, Jambi City.